PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Hotel Grand Zuri Pekanbaru) - Putri Nailil Husni; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT This study aims to determine how the effect of transformational leadership style and work motivation on employee performance at Grand Zuri Hotel Pekanbaru. Subjects in this study were 63 people who were all employees of the general department who had their respective duties from HRD. The hypothesis proposed in this study is that there is an influence between transormational leadership and work motivation on employee performance. The data collected in this study used two measuring instruments given to the subject, namely the linkert scale. The Transformational Leadership Style Scale is based on the theory of Bass in Kurniawan, (2011) and the Work Motivation scale is the Maslow scale (Robbins and Timothy, 2008) and the employee performance scale is the Megginson scale (Bangun, 2012), This study uses a simple liner regrelation analysis technique, which is a linear relationship between one independent variable (X) and the dependent variable (Y). Based on the results of the research, it shows that the hypothesis which states that there is transformational leadership (X1) and work motivation (X2) on employee performance (Y) at the Grand Zuri Hotel Pekanbaru is acceptable.This means that transformational leadership (X1) and work motivation (X2) on employee performance ( Y) This means that the better transormational leadership (X1) and work motivation (X2) on employee performance (Y) at the Grand Zuri hotel, Pekanbaru. This is evidenced by the results of research. So the value of Ftable at dfl = 2 and df2 = 61 is 2.84.This means that Fcount (11.344)> Ftable (2.84) with a significant 0.00